Correction: CD40 Activation Rescues Antiviral CD8+ T Cells from PD-1-Mediated Exhaustion. - Masanori Isogawa; Josan Chung; Yasuhiro Murata; Kazuhiro Kakimi; Francis V Chisari (PLoS Pathogens, 2016)
[This corrects the article DOI: 10.1371/journal.ppat.1003490.].